(untitled) (Revista revoluciones, 2021)
This article outlines a sketch on a character closely linked to José Gabriel Condorcanqui Tupac Amaru II. It aims to open new perspectives to the knowledge of the great rebellion of the Andes of 1780-1782, from a vision closer to the attitudes and vicissitudes of the life of the main actors of the popular commotion. It focuses on the figure of Mariano de la Barrera and also of Miguel Montiel, confidants close to Tupac Amaru in the years before the beginning of the rebellion. He ends up rescuing the tragic chapter of the exile he suffered from the Barrier and others after the movement was defeated.